Clinical values of oblique lumbar interbody fusion on the treatment of single-level degenerative lumbar diseases - Yu, Yu (Frontiers in Surgery, 2024)
ObjectivesMinimally invasive transforaminal lumbar interbody fusion (Mis-TLIF) and oblique lumbar interbody fusion (OLIF) are increasingly replacing traditional approaches. This study aimed to compare the clinical outcomes of OLIF and Mis-TLIF in treating single-level degenerative lumbar diseases.MethodsPatients with single-level degenerative lumbar diseases underwent either OLIF (30 patients) or Mis-TLIF (30 patients). Surgical data, including operation time, blood loss, postoperative drainage, and postoperative bed rest duration, were collected. Clinical outcomes were assessed using the Oswestry disability index, the visual analog scale scores for low back pain and leg pain, and Japanese Orthopaedic Association scores for daily ability, along with monitoring of complications.ResultsThe OLIF group showed significantly shorter operative times, less blood loss, reduced postoperative drainage, and shorter bed rest durations than the Mis-TLIF group. At the 1-month follow-up, OLIF patients also demonstrated significantly better clinical outcome scores than Mis-TLIF patients. No significant differences were observed between OLIF and Mis-TLIF patients before surgery and after 3 months. Furthermore, lumbar lordosis and disc height were significantly greater in the OLIF group at the final follow-up.ConclusionsBoth OLIF and Mis-TLIF achieved satisfactory and effective long-term clinical outcomes for single-level lumbar degenerative diseases. However, OLIF resulted in less tissue damage, reduced bleeding, better short-term clinical outcomes, and improved recovery of segmental lordosis compared to Mis-TLIF. Therefore, OLIF appears to be the preferable option over Mis-TLIF.